Ability of Accruals Prediction Models on the Basis of Jones Model in Prediction of Abnormal Accruals and (مجله دانش حسابداری, 2013)
To estimate abnormal accruals, prior researches employed a wide variety of models and estimation procedures. We evaluate the performance of three representative models, modified Jones model (MJ), MJ with operating cash flows (MJOCF), and MJ with return on assets (MJROA), using multi regression model and a sample with 80 active companies in Tehran Stock Exchange (TSE). In addition, we investigated accrual anomaly, using MJ with operating cash flows (MJOCF), and MJ with return on assets (MJROA). The result showed that the best model for perspective abnormal accrual is the MJOCF model, and that MJOCF shows less accrual anomaly.